Muslim burial practices and Belgian legislation and regulations: a comparative literature review. (2nd October 2017) - Ahaddour, Chaïma; Broeckaert, Bert
Abstract: Belgian burial regulations are challenged by a growing Muslim population. In this review, we first provide an overview of Muslim burial practices. Second, we describe how Belgian public policies have addressed the topic of Islamic burial. Third, we compare Belgian burial regulations and their impact on Islamic burial with those of the neighbouring countries. Literature published between 1997 and 2016 has been included. Repatriation to the country of origin seems to be a result of a number of factors (religious and financial barriers; …). Differences are observed between policy levels and countries due to different interpretations of neutrality and religious freedom.